Random Sign Repetition Time-Hopping UWB with Multiuser Detection - Choi Jinho (EURASIP Journal on Wireless Communications and Networking, 2005)
A modified time-hopping (TH) ultra-wideband (UWB), called the random sign repetition TH-UWB, is considered to improve the performance of the minimum mean square error (MMSE) multiuser detector. We show that the increase of dimension or the number of repetitions is important to improve the performance of the MMSE detector in the random sign repetition TH-UWB for either coded or uncoded signals.